Penerapan Sistem Manajemen Pendidikan Berbasis Total Quality Management Di Lembaga Pendidikan Islam: Studi Kasus Mts Miftahul Huda Dongos Jepara - Wilantika, Nurul; Sukarman, Sukarman; Nailizzulfa, Ellisa; Fuad, M. Kholil Tsamrotul; Faizin, Zein (JURNAL MANAJEMEN PENDIDIKAN, 2026)
DEPARTMENT OF ISLAMIC EDUCATION MANAGEMENT, GRADUATE PROGRAM, UNIVERSITAS ISLAM NAHDLATUL ULAMA JEPARA, JEPARA, CENTRAL JAVA, INDONESIAThis study aims to analyze the implementation of a Total Quality Management (TQM) based education management system at MTs Miftahul Huda Dongos, Jepara. The institution has made significant efforts to realize its vision of “Developing a Generation that Is Religiously Devout and Competent in Science and Technology.” TQM, as a management philosophy that emphasizes continuous improvement and stakeholder satisfaction, is considered relevant for enhancing the overall quality of madrasah education. Using a case study approach, the findings indicate that TQM is implemented through quality planning aligned with the institutional vision, transformational democratic leadership of the principal, Mr. Arif Nashiruddin, M.Pd., a dual focus on the quality of educational processes (religiosity and science and technology), and continuous improvement mechanisms in teaching and learning activities. The implementation of TQM is further strengthened by a participatory organizational culture and the integration of Islamic values.